Financial Toxicity of Cancer Care: It's Time to Intervene - Zafar, S Yousuf (JNCI : Journal of the National Cancer Institute, 2016)
Evidence suggests that a considerably large proportion of cancer patients are affected by treatment-related financial harm. As medical debt grows for some with cancer, the downstream effects can be catastrophic, with a recent study suggesting a link between extreme financial distress and worse mortality. At least three factors might explain the relationship between extreme financial distress and greater risk of mortality: 1) overall poorer well-being, 2) impaired health-related quality of life, and 3) sub-par quality of care. While research has described the financial harm associated with cancer treatment, little has been done to effectively intervene on the problem. Long-term solutions must focus on policy changes to reduce unsustainable drug prices and promote innovative insurance models. In the mean time, patients continue to struggle with high out-of-pocket costs. For more immediate solutions, we should look to the oncologist and patient. Oncologists should focus on the value of care delivered, encourage patient engagement on the topic of costs, and be better educated on financial resources available to patients. For their part, patients need improved cost-related health literacy so they are aware of potential costs and resources, and research should focus on how patients define high-value care. With a growing list of financial side effects induced by cancer treatment, the time has come to intervene on the "financial toxicity" of cancer care.